Effects of folic acid and cobalt sulphate supplementation on growth performance, nutrient digestion, rumen fermentation and blood metabolites in Holstein calves. Issue 9 (14th May 2022) - Liu, Yongjia; Zhang, Jing; Wang, Cong; Liu, Qiang; Guo, Gang; Huo, Wenjie; Chen, Lei; Zhang, Yanli; Pei, Caixia; Zhang, Shuanlin
Abstract: To investigate the influences of cobalt (Co) and folic acid (FA) on growth performance and rumen fermentation, Holstein male calves ( n 40) were randomly assigned to four groups according to their body weights. Cobalt sulphate at 0 or 0·11 mg Co/kg DM and FA at 0 or 7·2 mg/kg DM were used in a 2 × 2 factorial design. Average daily gain was elevated with FA or Co supplementation, but the elevation was greater for supplementing Co in diets without FA than with FA. Supplementing FA or Co increased DM intake and total-tract nutrient digestibility. Rumen pH was unaltered with FA but reduced with Co supplementation. Concentration of rumen total volatile fatty acids was elevated with FA or Co inclusion. Acetate percentage and acetate to propionate ratio were elevated with FA inclusion. Supplementing Co decreased acetate percentage and increased propionate percentage. Activities of xylanase and α -amylase and populations of total bacteria, fungi, protozoa, Ruminococcus albus, Fibrobacter succinogenes and Prevotella ruminicola increased with FA or Co inclusion. Activities of carboxymethyl-cellulase and pectinase increased with FA inclusion and population of methanogens decreased with Co addition. Blood folates increased and homocysteine decreased with FA inclusion. Blood glucose and vitamin B12 increased with Co addition. The data suggested that supplementing 0·11 mg Co/kg DM in diets containing 0·09 mg Co/kg DM increased growth performance and nutrient digestibility but had no improvement on the effects of FA addition in calves.